Versatile Layered Hydroxide Precursors for Generic Synthesis of Cu‐Based Materials. Issue 1 (6th October 2022) - Jang, Wonsik; Kim, Jihun; Yoon, Sinmyung; Kim, Miri; Kim, Jongkyoung; An, Kwangjin; Cho, Seungho
Abstract : The ability to mix multiple elements in a structure is crucial for obtaining Cu‐based nanostructures and microstructures with desirable physicochemical properties. Precursors containing multiple metal cations, such as layered double hydroxides, have been used for the synthesis of multielement materials. However, these precursors experience difficulty containing large cations, which limits the functionalities of the derived materials. Herein, the development of Cu‐based hydroxy double salts (HDSs), versatile precursors that accommodate a broad range of metal cations with homogeneous distributions, is reported. Up to 25 different metal cations are mixed with Cu in an HDS single phase, individually and simultaneously. The HDSs further exhibit useful properties with respect to anion exchange, exfoliation, and phase transformation to metal oxides. During the metal oxide transformation process, the formed crystal structures are mainly dependent on the ionic radius of the secondary metal cations. To prove their utility as precursors, the metal oxides derived from the HDSs are tested and found that they exhibited high catalytic activities for CO oxidation. This study significantly expands the compositional and structural freedom of Cu‐based multi‐elemental materials. Abstract : Versatile precursors for generic synthesis of Cu‐based materials are developed, which can contain a broad range of metal cations (26 different cations). They have many chemical and structural degrees of freedom, which can be achieved by anion exchange, exfoliation, and phase transformation. To prove their utility as precursors, 15 derived oxides exhibiting high catalytic CO oxidation activities are tested.